PENGEMBANGAN INSTRUMEN ASESMEN AUTENTIK KETERAMPILAN MENULIS TEKS CERPEN DAN TEKS FABEL UNTUK SISWA SMP/MTS YANG MENGIMPLEMENTASIKAN KURIKULUM 2013 - Kukuh Fadliyatis S; Titik Harsiati; Muakibatul Hasanah (Graduate School of Universitas Negeri Malang, 2016)
The purpose of this research is to produce a text writing skills assessment instrument of short stories and fables and text describe the results of a reliability test instrument products. This type of research is the development of research development model adaptation O'Malley and Pierce (1994). There are four products in this study: (1) the task of writing the authentic text of the short story, (2) guide teachers for writing text stories, (3) the task of writing an authentic text fable, and (4) guide teachers for writing text fable. The research result of this development: (1) product assessment instrument text short stories get a correlation value of 0, 829 and (2) product assessment instrument text fable obtain a correlation value of 0, 761. Correlation values obtained product assessment instrument text stories and fables text> 0.05 means product assessment instrument text short stories and fables have high reliability.Tujuan penelitian ini yaitu menghasilkan instrumen asesmen keterampilan menulis teks cerpen dan teks fabel dan mendeskripsikan hasil uji reliabilitas produk instrumen. Jenis penelitian ini adalah penelitian pengembangan dengan model pengembangan adaptasiO’Malley dan Pierce (1994). Ada empat produk dalam penelitian ini yakni (1) tugas menulis autentik teks cerpen, (2) panduan guru menulis untuk teks cerpen, (3) tugas menulis autentik teks fabel, dan (4) panduan guru untuk menulis teks fabel. Hasil penelitian pengembangan ini yaitu (1) produk instrumen asesmen teks cerpen mendapatkan nilai korelasi 0, 829 dan (2) produk instrumen asesmen teks fabel mendapatkan nilai korelasi 0, 761. Nilai korelasi yang diperoleh produk instrumen asesmen teks cerpen dan teks fabel > 0.05 artinya produk instrumen asesmen teks cerpen dan teks fabel memiliki reliabilitas yang tinggi.